PENGARUH NATTOKINASE TERHADAP DAYA KERJA Metformin HCl DALAM MENURUNKAN KADAR GLUKOSA DARAH PADA TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR WISTAR - M Sandila Okta; Vivi Sofia (Universitas Ahmad Dahlan, 2013)
Interaction of modern drug and traditional drug is an issue that needs to be examined, not least in the treatment of diabetes mellitus. Nattokinase is a nutraceutical product that can be used in conjunction with antidiabetic oral drugs that allows the interaction. This study aims to determine the effect of Nattokinase against their power Metformin HCl in decreasing of blood glucose levels male white rats (Rattus norvegicus) Wistar. This study uses an oral glucose tolerance test with glucose loading dose of 4.5 g/kg. Animals test used were white male Wistar rats aged 2-3 months weighing 150-200 g, 20 rats were divided into 4 groups, each group consisted of 5 rats. Group I as a negative control group was given tween 80 - span 80, group II as a positive control group was given metformin HCl doses of 45 mg/kg, group III was given Nattokinase dose 300 mg/kgBB, group IV given nattokinase 300 mg/kgBB 1 hour then were given metformin HCl. 30 minutes later all treatment of groups were given glucose. When treatment is considered as a time at-0. The given of glucose is considered as the time at-30. Blood sampling via the tail at 0, 30, 60, 120, and 180. Blood glucose levels was measured with the Easy Touch. The effect of decreasing blood glucose levels indicated by the value of LDDK0-180 (Regional Area Under the Curve minute 0 to minute 180 of the graph time vs blood glucose levels). The data can be tested statistically by Kruskal-Wallis and Mann Whitney with a level of 95%. The results showed that administration of Metformin HCl after 1 hour administration Nattokinase can be decreased 52.22% of Metformin HCl.